The mediating role of empathy in relationships between conscientious intelligence and perceptions of spiritual care among Turkish nurses; a structural equation modelling - Seçil Ergin Doğan; Hakime Aslan; Abdurrahman Akçin (BMC Nursing)
Abstract Aim This study was conducted to evaluate the relationship between nurses’ conscientious intelligence, their empathy levels and perception of spirituality and spiritual care. The study also aimed to determine whether empathy mediates the relationship between conscientious intelligence and perceptions of spirituality and spiritual care. Materials and methods This is a descriptive study with correlational design. This study was conducted with 315 nurses working in a training and research hospital in the east of Turkey. ‘Conscientious Intelligence Scale (CIS)’, ‘Empathy Quotient Scale (EQS)’ and ‘Spirituality and Spiritual Care Rating Scale (SSCRS)’ are data collection tools. Data analysis was performed using SPSS version 25 and AMOS version 26 software. Results It was determined that there was a weak positive significant relationship between nurses’ conscientious intelligence (CIS) levels and empathy levels (EQS) (r:0.219, p < 0.001), a moderate positive significant relationship between conscientious intelligence (CIS) and perceptions of spirituality and spiritual care (SSCRS) (r:0.373, p < 0.001), and a moderate positive significant relationship between empathy level (EQS) and perceptions of spirituality and spiritual care (SSCRS) (r:0.351, p < 0.001). In addition, empathy mediates the relationship between conscientious intelligence and perception of spirituality and spiritual care (Two Tailed Significance value is 0.02 and below 95% confidence interval). Conclusion As a result, a significant relationship was found between nurses’ levels of conscientious intelligence and their perceptions of empathy and perceptions of spirituality and spiritual care. Additionally, empathy was found to mediate the relationship between conscientious intelligence and perceptions of spirituality and spiritual care. In this context, it is recommended that training programmes be organised to improve nurses’ conscientious intelligence and spiritual care perceptions, and that various strategies such as reflective thinking and case-based training be applied to improve empathy skills. Furthermore, spiritual care, conscientious values, and communication skills should be incorporated more into nursing education curricula. Clinical trial number Not applicable.